2018
DOI: 10.11118/actaun201866030701
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Meat Quality of Prestice Black-Pied and (Landrace × Large White) × Duroc Pigs

Abstract: The objective of the performed experiment was to evaluate growth performance and selected carcass traits and meat quality parameters in pigs of a native Czech breed Prestice Black-Pied pig (PB) and a commercial hybrid (H) used for meat production. The observation included 40 pigs, 20 pigs of the native breed PB and 20 pigs of the hybrid combination. The PB piglets showed higher (P ≤ 0.05) birth weight than the H piglets. The lifetime weight gain was higher (P ≤ 0.01) in the H pigs than in the PB pigs. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
2
0
1
Order By: Relevance
“…The results of the present study are consistent with the results regarding other local breeds reared outdoors and fed either grass, acorn, or chestnut [48], as well as with reports on the fatty acid composition of Prestice Black-Pied breed and Puławska pig breeds raised indoors [1,57]. Furthermore, in their investigation on the differences between the French local Basque breed and the Large White breed reared in conventional and production systems to LW of 145 kg, Lebret et al (2014) [39] found that Basque pigs reared outdoors had increased MUFA and PUFA levels and a decreased SFA share in total fatty acids compared to both Basque animals reared intensively and Large White pigs kept in a conventional production system.…”
Section: Chemical Composition and Fatty Acid Profilesupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study are consistent with the results regarding other local breeds reared outdoors and fed either grass, acorn, or chestnut [48], as well as with reports on the fatty acid composition of Prestice Black-Pied breed and Puławska pig breeds raised indoors [1,57]. Furthermore, in their investigation on the differences between the French local Basque breed and the Large White breed reared in conventional and production systems to LW of 145 kg, Lebret et al (2014) [39] found that Basque pigs reared outdoors had increased MUFA and PUFA levels and a decreased SFA share in total fatty acids compared to both Basque animals reared intensively and Large White pigs kept in a conventional production system.…”
Section: Chemical Composition and Fatty Acid Profilesupporting
confidence: 92%
“…The obtained IMF values for the meat from the NAT chain were higher than those reported for Krškopolje [55], Celta [56] and Prestice Black-Pied [57] pigs, but they were lower than those for Iberian [58] and Laiwu [59] pigs.…”
Section: Chemical Composition and Fatty Acid Profilecontrasting
confidence: 73%
“…This experiment was performed with the aim of evaluating the effect of providing outdoor access to PBP on their growth, carcass characteristics, and longissimus lumborum muscle meat quality. From the conclusions of previous preliminary studies, where PBPs were compared with a commercial hybrid line in two different production systems, the outdoor rearing system proved to be a more suitable alternative system for this indigenous breed [32].The growth performance and carcass traits evaluated in this study were comparable to those results obtained from the PBP population in previous studies [33,34]. Regardless of the production system used, the results show that PBPs were able to utilize a local protein feed.…”
Section: Discussionsupporting
confidence: 71%